The degree of ownership of the school principals in Zarqa Governorate for the skill of managing school crises from their point of view. - Al-Mushagiba, Metib (Journal of Educational and Psychological Sciences, 2018)
The study aimed to revealing the degree of ownership of school schools in Zarqa Governorate for the skill of managing school crises from their point of view. In order to achieve the objectives of the study, the researcher used the descriptive method. He constructed a tool for the study which consisted of (24) Selection of random sample consisted of (125) managers and managers. The results indicated that the degree of ownership of school schools in the province of Zarqa for the skill of school crisis management from their point of view on the tool as a whole was high (4.14). The ranking of the fields ranked in descending order according to the level of fields: the field of confrontation, (4.09), containment area, and reached (4.00). The results showed that there were no statistically significant differences at the level of (α = 0.05) in the degree of ownership of school schools in Zarqa governorate for the skill of school crisis management due to gender variable. In the light of the results, a number of recommendations and proposals were presented to increase the degree of ownership of crisis management skills in the schools of Zarqa and the whole of the Kingdom of Jordan.